A hipotética linguagem ideal de Platão - Santos, Maria Carolina Alves Dos (Universidade Estadual Paulista, Departamento de Filosofia, 2003)
For a discourse on the spectacle of the transcendental world to be received in its comprehensible and coherent totality, its needs to get rid of the arbitrariness of the dominion of tremulous shapes of the sensitive, which is merely the sphere of opinions. This is what Plato suggests, following the course of reflection of the first thinkers: in order to compensate the deficiencies that entail elision of reality and to transform language into a vehicle of authentic intellection of the fundamental concepts of philosophical thinking, he sets it into the center of a rigorous speculation. In the same way as his predecessors Heraclitus and Parmenides, the philosopher reveals logofilia at exerting himself to build a new discursive structure, different from that of common man and thereby stirring, in the field of philosophy, a revolution that had become indispensable: he elaborates a founding model - the beginning of a permanent order as the prelude to the edification of a formal and abstract language that refers to entities that the majority of humans cannot visualize by themselves. Only through it will the universal truth of the divine Forms be able to shine, which, at lending their names to the endless series of sensible particulars, clarifies them and confers them signification. Through the theories he develops based on them and exposes in the Dialogues,the philosopher aims at inducing the reader to prepare himself to methodically operate the conversion of his soul to the level of these super-sensitive ideal beings and grasp, thus, the reality that founds and turns everything cognizable.

Para que um discurso sobre o espetáculo do mundo transcendente seja acolhido como totalidade inteligível e coerente, urge desvencilhar-se da arbitrariedade do domínio de trêmulos contornos do sensível, esfera de opiniões apenas. É o que propõe Platão, na esteira das reflexões dos primeiros pensadores: para suprir deficiências que causam a elisão da realidade e transformar a linguagem num veículo de intelecção autêntica dos conceitos essenciais de um pensar filosófico, ele a coloca no centro de uma especulação rigorosa. Tal como seus antecessores Heráclito e Parmênides, Platão revela logofilia ao empenhar-se na construção de uma nova estrutura discursiva, diferente daquela do homem comum, desencadeando no campo da Filosofia uma revolução que se tornara indispensável: elabora um modelo fundador - princípio de uma ordem permanente propedêutica à construção de uma linguagem formal e abstrata - referente a entes que os homens, na maioria, por si mesmos não conseguem visualizar. Somente nela poderá reverberar a verdade universal das Formas que, ao emprestarem seus nomes à infindável série dos particulares sensíveis, os clarifica e lhes confere significação. Com as teorias que a partir das Formas desenvolve e expõe nos Diálogos, o filósofo visa induzir o leitor a preparar-se para operar, metodicamente, a conversão de sua alma ao plano desses seres ideais, supra-sensíveis, e apreender, assim, a realidade que tudo fundamenta e torna cognoscível.
Plato's hypothetical ideal language
Keywords: Plato; discourse; metafisics; theology; language of the mysteries; dialectics; Platão; discurso; metafísica; teologia; linguagem dos mistérios; dialética